WEBSITE DESIGN APPLICATIONS USING BIOGRAPHY CHRISYE MICROSOFT FRONTPAGE 2003 - Yoeni Ana Kurniati; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2008)
Media information is a means to convey a message or information that we havereceived both orally and in writing, and various kinds such as newspapers, television,radio, and computers.Information plays a very important for human life. The required information must beinformation very quickly, accurately, and can be accounted for authenticity by many,especially among people for business, entertainment, and various other information.The Internet is a global collection of (global) network of thousands of computers andmillions of personal computers that are managed independently. Internet easy to useby anyone, even those that have only minimal capabilities.Web is an information delivery using Internet technology. With the web, we caninteract in a vast space. Until now, the website is very popular, but its use is requiredin a design. And the design is less attractive if not equipped with an image, texture,color, color effects, and so forth.